Evaluation on street furniture in Jalan Dhoby and Jalan Tan Hiok Nee, Johor Bahru, Johor / Azizul Hakeem Zulkiflee - Azizul Hakeem, Zulkiflee (2020)
This study is being conducted about the evaluation of street furniture in Jalan Dhoby and Jalan Tan Hiok Nee, Johor Bahru. The study area covered the area of Jalan Dhoby and Jalan Tan Hiok Nee which it consists of commercial area. For the literature review, it will be explain on the elements of street furniture that need to be evaluate. The literature review also reviews on the design and principle that need to be implement in this study. Besides that, the data collection method used to carry out the study are questionnaire and observation survey. A total of 30 respondents are required in gathering the data. Each of those method provides a different output for this study. So, for the observation survey method is carried out by making a detailed observation and inspection on site which is Jalan Dhoby and Jalan Tan Hiok Nee, Johor Bahru, Johor. Data analysis and findings has been carried out after the data collection is completely done, the findings from the analysis will be the basic preparation of making an appropriate recommendation and conclusion. The recommendation that has been set up is mostly are to develop and enhance the street furniture in Jalan Dhoby and Jalan Tan Hiok Nee. It is to create the sense of place and represent the identity of the place at the same time to increase the users perception on the street furniture in Jalan Dhoby and Jalan Tan Hiok Nee, Johor Bahru, Johor.